Mathematische Modelle in der Biologie: 1.6. bis 7.6.1975 - Hadeler, Karl-Peter; Jäger, Willi; Werner, Helmut (Tagungsbericht, 1975)
W. Alt, Münster; J. Batt, München; W. Bühler, Mainz; J. E. Cohen, Cambridge; B. D. Coleman, Pittsburgh; Ch. Conley, Madison; K. Dietz, Genf; L. Edler, Mainz; J. W. Evans, La Jolla; P. C. Fife, Tucson; K. P. Hadeler, Tübingen; U. an der Heiden, Tübingen; F. C. Hoppensteadt, New York; W. Jäger, Heidelberg; K. Jänich, Regensburg; N. Kaplan, Kopenhagen; R. Keller, Regensburg; L. Lander, Regensburg; D. Ludwig, Vancouver; H. Maurer, Köln; H. Meinhardt, Tübingen; B. Mellein, Mainz; P. de Mottoni, Rom; I. Nasell, Stockholm; F. Poggio, Tübingen; T. Poston, Genf; R. Repges, Aachen; G. H. Renninger, Guelph; H. L. Resnikoff, Münster; F. Rothe, Tübingen; L. A. Segel, Rehovot; B. D. Sleeman, Dundee; L. M. Sonneborn, Bern; D. Steinhausen, Münster; H. Thieme, Münster; R. Thom, Bures-sur-Yvette; W. Vogel, Bonn; H.-O. Walther, München; P. Waltman, lowa City; H. Werner, Münster; A. Wörz, Tübingen; E. C. Zeeman, Coventry; R. Zielke, Tübingen; B. Zwahlen, Lausanne